Analisis Yuridis Terhadap Tindak Pidana Korupsi yang Melibatkan Pengurus Korporasi (Studi Kasus Putusan PN Jakarta Pusat No.49/Pid.Sus-Tpk/2024) - Budiman, Arif; Ajie, Bintang Wicaksono (Neolectura, 2025)
This study analyzes the legal application in a corporate corruption case involving the director of PT ADI INTI MANDIRI, as outlined in the Central Jakarta District Court Decision No. 49/Pid.Sus-TPK/2024. The case arose from irregularities in the procurement of a monitoring system for Indonesian migrant workers under the Directorate of Overseas Employment, resulting in significant state losses. This analysis demonstrates that corporations can be held criminally liable for the actions of their executives, particularly in cases involving collusion and procurement manipulation mechanisms. In the court decision, the defendant was sentenced to imprisonment, fines, and restitution. This study employs a normative juridical research method to examine the ruling and relevant regulations. It highlights the importance of robust internal control systems to prevent abuses of authority within corporations. The findings reveal that strict law enforcement, supported by collaboration between the government, private sector, and civil society, is essential to prevent corrupt practices and establish a transparent and accountable business environment in Indonesia.